IMPROVING LEARNING OUTCOMES OF CLASS II MI AL KAUTSAR STUDENTS USING JARIMATICS METHODS IN LESSONS MULTIPLICATION MATHEMATICS IN 2023/2024 - Rabiah Adawiyah; Muhammad Ali Akbar (PT PUBLIKASI INSPIRASI INDONESIA, 2023)
Rabiah Adawiyah NIM. 858412777, IMPROVING STUDENTS' MATHEMATICS LEARNING OUTCOMES ON MULTIPLICATION MATERIAL USING THE MATHEMATICS METHOD IN CLASS II MI AL KAUTSAR ACADEMIC YEAR 2023/2024. The low skills think creative students ' eyes lesson mathematics material multiplication class II MI Al Kautsar background back study This . Based on results interview with the class II teacher that learning mathematics during This seldom using learning media as tool help Study . So that researcher do repair learning with using concrete media . Study This own objective to : 1) know How use method Jarimatika to improve creative thinking skills on Multiplication material in IIMIS Al- Kautsar class. know How enhancement Skills think creative material Multiplication number round student class II MIS Al Kautsar use finger method .